Vocal Colour in Blue: Early Twentieth-Century Black Women Singers as Broadway’s Voice Teachers - Asare, Masi (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2020)
This essay invokes a line of historical singing lessons that locate blues singers Bessie Smith and Ethel Waters in the lineage of Broadway belters. Contesting the idea that black women who sang the blues and performed on the musical stage in the early twentieth century possessed “untrained” voices—a pervasive narrative that retains currency in present-day voice pedagogy literature—I argue that singing is a sonic citational practice. In the act of producing vocal sound, one implicitly cites the vocal acts of the teacher from whom one has learned the song. And, I suggest, if performance is always “twice-behaved,” then the particular modes of doubleness present in voice point up this citationality, a condition of vocal sound that I name the “twice-heard.” In considering how vocal performances replicate and transmit knowledge, the “voice lesson” serves as a key site for analysis. My experiences as a voice coach and composer in New York City over two decades ground my approach of listening for the body in vocal sound. Foregrounding the perspective and embodied experience of voice practitioners of colour, I critique the myth of the “natural belter” that obscures the lessons Broadway performers have drawn from the blueswomen’s sound.